Long-Term Profiles of Bullying Victims and Aggressors: A Retrospective Study - Valera-Pozo, Mario; Flexas, Albert; Servera, Mateu; Aguilar-Mediavilla, Eva; Adrover-Roig, Daniel (Frontiers in Psychology, 2021)
The present work explored the long-term characteristics of bullying victims and aggressors using a retrospective design. A sample of 138 adults of different ages completed an on-line protocol that included measures of bullying and victimization, substance use, sensitivity to reward and punishment, social skills, antisocial behavior, emotional regulation strategies, psychological adjustment, self-esteem, and risk of suicide. The sample was divided into three groups (victims, aggressors and controls) based on their responses to bullying-related questions. A set of Multiple Analyses of Variance with group was carried out for each dependent variable. Victims and aggressors did not significantly differ in their self-reported substance consumption. Victims showed lower psychological adjustment, higher emotional lack of control and rejection, lower self-esteem, and a larger frequency of suicidal thoughts (in the past) than controls. Aggressors showed higher sensitivity to reward, larger communicational and relational skills, and higher emotional insensitivity. Accordingly, the logistic regression analysis identified sensitivity to reward and psychological maladjustment as the main predictors of aggressor and victim profiles, respectively. The present results are discussed considering current theories of bullying and may help to improve prevention programs for this relevant social scourge.